The Relationship Between Consumer Interest, Satisfaction, Location, and Capital on Street Vendor Income in Makassar City - Thamrin Tahir; Muhammad Ilyas Thamrin Tahir (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the elements that influence shopper interest, fulfillment, breadth and capital on seller payments in the city of Makassar during the Coronavirus period with an exploration center around the attributes, inspiration and system of street vendors. This research used a subjective investigation strategy with 5 respondents not arranged according to exploration standards. This research uses qualitative methods and a case study approach. The main techniques for using data are observation and interviews. Gather information by utilizing strategies for top-down perception and meetings. The research results show that the quality of sales in the city of Makassar by individuals whose teaching level is at the secondary school level is 41.86%. Long time selling for 4 hours a day, with typical pay under 500 thousand per day. The side effects of this research are expected to increase the abundance of information for comparable exploration, as well as to grow information in Monetary Topography investigations, especially in the field of work